Risk factor of postoperative pulmonary complications after colorectal cancer surgery: an analysis of nationwide inpatient sample - Liping Huang; Junli Luo; Yifan Wang; Lu Gan; Nuo Xu; Jinzi Chen; Cai Li (Scientific Reports)
Abstract To investigate the incidence rate, risk factors, and clinical implications of postoperative pulmonary complications (PPCs) in patients undergoing colorectal cancer surgery (CRC). The study extracted data from the National Inpatient Sample (NIS) between 2010 and 2019. Patients’ data were analyzed to identify predictors of PPCs, and the association between possible factors and PPCs were also assessed. A total of 169,067 CRC surgery patients were included and 15,494 (9.16%) were diagnosed with PPCs in the study. Our study found that age, gender, number of comorbidities, type and location of hospital, and certain preoperative comorbidities, such as fluid and electrolyte disorders (odd ratio [OR] 2.53), coagulopathy (OR 2.16), congestive heart failure (OR 1.91), and chronic pulmonary disease (OR 1.57) were the risk factors of PPCs. In addition, postoperative complications, such as continuous mechanical ventilation (OR 8.18), sepsis (OR 4.46), deep vein thrombosis (OR 4.17) and shock (OR 4.07) were the most important risk factors of PPCs. PPCs prolonged the length of hospital stay (14 days vs. 6 days) and led to a higher mortality rate (13.04% vs. 1.20%). Optimizing perioperative care practices are essential steps to reduce the incidence rate of PPCs in CRC patients.